2019
DOI: 10.4149/gpb_20190281
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resveratrol on oxidative ovary-damage induced by methotrexate in rats (Resveratrol oxidative ovary-damage)

Abstract: Methotrexate (MTX) is a commonly used folic acid antagonist for the treatment of neoplasia and some autoimmune diseases. Resveratrol has important anti-inflammatory, antioxidant and immunomodulatory properties. The aim of this study was to investigate the effects of resveratrol on MTX-induced ovary-damage and oxidative stress in rats. We hypothesized that supplement of resveratrol could counteract MTX-induced cytotoxicity in rat ovary. Albino Wistar female rats were randomly divided into three groups: Healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…In our study, histopathological evaluation revealed that ovarian damage in the MTX + RES group was significantly milder than in the MTX group In addition, the decrease in the number of follicles seen in MTX groups increased in MTX+RES groups. Similar to our study in the literature, Ata et al (36) reported the effects of RES on MTX-induced ovarian damage. In this study, RES was shown to protect the ovary from damage caused by MTX.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, histopathological evaluation revealed that ovarian damage in the MTX + RES group was significantly milder than in the MTX group In addition, the decrease in the number of follicles seen in MTX groups increased in MTX+RES groups. Similar to our study in the literature, Ata et al (36) reported the effects of RES on MTX-induced ovarian damage. In this study, RES was shown to protect the ovary from damage caused by MTX.…”
Section: Discussionsupporting
confidence: 92%
“…It has been stated in previous studies that biochemical findings that reflect oxidative stress coincide with histopathological findings 14 . As the literature suggests, MDA and tGSH are biochemical parameters that commonly used to identify oxidative damage in the ovarian tissue 15,16 . Histopathological findings showing increased MDA and reduced tGSH levels in ovarian tissues were reported as indicative of progressive tissue damage in a previous study 17 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RES may stimulate ovarian activity and slow ovarian aging. In POF animal models, RES activates primordial follicles, increases the quantity of primary, primordial, and developing follicles, enhances granulosa cell proliferation, reduces ovarian inflammatory response, preserves the ovarian structure, and prevents oocyte and granulosa cell damage [55,56].…”
Section: Discussionmentioning
confidence: 99%